Jordan Derivations on Lie Ideals of Semiprime ?-Rings - Rahman, Md Mizanor; Paul, Akhil Chandra (GANIT: Journal of Bangladesh Mathematical Society, 2016)
Let M be a 2-torsion free semiprime G-ring satisfying the condition a?b?c = a?b?c,?a, b, c ?M and ?, ? ??. Let U be an admissible Lie ideal of M that is, u?u ? U,?u ? U, ? ?G and U ?Z(M), the centre of M. If d : M -> M is an additive mapping such that d is a Jordan derivation on U of M, then d is a derivation on U. GANIT J. Bangladesh Math. Soc.Vol. 34 (2014) 35-46